2020
DOI: 10.3390/ma13092186
|View full text |Cite|
|
Sign up to set email alerts
|

Microstructure and Degradation of Mortar Containing Waste Glass Aggregate as Evaluated by Various Microscopic Techniques

Abstract: The primary aim of this article is to focus on the alkali-silica reaction (ASR) in mortar specimens containing coloured waste glass used as an aggregate. Mortar expansion was measured using the ASTM C 1260 accelerated test procedure until the specimens disintegrated. Special attention was paid to the microscopic examination of the damaged mortar. Various methods were used for this purpose, including optical microscopy in reflected and transmitted light with one and two crossed polarizers. The specimens were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The addition of waste glass as a partial substitute to fine aggregate has been reported to improve the mechanical properties of heat resistant cementitious mortars [ 15 ]. Additionally, based on a review of several scholarly papers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], we can state that waste glass can be used, depending on its fineness, as a partial replacement to fine aggregate or cement; in the latter case, playing a role of a binder.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of waste glass as a partial substitute to fine aggregate has been reported to improve the mechanical properties of heat resistant cementitious mortars [ 15 ]. Additionally, based on a review of several scholarly papers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], we can state that waste glass can be used, depending on its fineness, as a partial replacement to fine aggregate or cement; in the latter case, playing a role of a binder.…”
Section: Introductionmentioning
confidence: 99%
“…The control mixes were produced with fly ash, which has been successfully used in concrete production for many years. From the observations made during quality control of works and materials used for the national roads in Poland, we knew that the content of fly ash in concretes can reach 50% by weight of cement (on Recent publications [4][5][6][7][8][9][10][11][12][13] indicate an increasing interest in waste glass and its application in concrete production. It is worth noting that use of glass as an addition to concrete can be limited due to the risk of alkali-silica reaction (ASR) [5][6][7]13].…”
Section: Methodsmentioning
confidence: 99%
“…From the observations made during quality control of works and materials used for the national roads in Poland, we knew that the content of fly ash in concretes can reach 50% by weight of cement (on Recent publications [4][5][6][7][8][9][10][11][12][13] indicate an increasing interest in waste glass and its application in concrete production. It is worth noting that use of glass as an addition to concrete can be limited due to the risk of alkali-silica reaction (ASR) [5][6][7]13]. Some studies have demonstrated that particles of glass greater than 1 mm make concrete more prone to ASR-induced damage [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these tests should be classified as semi-destructive tests. On their basis, it is possible to identify the causes of cracks [ 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%